2019
DOI: 10.1017/s1743923x19000217
|View full text |Cite
|
Sign up to set email alerts
|

Public Support for Increasing Women and Minority MPs

Abstract: Most democracies fail to provide equal representation and tend to have an overrepresentation of men from the upper class and the majority racial or ethnic group. We investigate public support for increasing the number of women and indigenous Māori members of parliament (MPs) in the New Zealand Parliament, both in general and through specific mechanisms such as quotas and reserved seats. We offer three explanations: descriptive (group identity), substantive (issue alignment), and symbolic (socioeconomic and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
(62 reference statements)
3
10
0
Order By: Relevance
“…Yet, the main literature on citizen support for gender quotas, and more broadly women in politics, do not explore whether citizens might support gender quotas for patronizing, or potentially sexist, reasons (but see Pereira & Porto, 2020). Previous investigations emphasize attitudes toward gender equality (Beauregard, 2018; Gidengil, 1996; Keenan & McElroy, 2017), support for government involvement (Barnes & Córdova, 2016), partisanship and ideology (Dubrow, 2011), elite cues (Morgan & Buice, 2013), or a desire for descriptive and substantive representation (Allen & Cutts, 2016; Bolzendahl & Coffé, 2020) as explanations for quota support. We further explore a crucial set of explanations for understanding gender‐quotas support that nuances the previous understanding that greater commitment toward gender equality should be linked with greater support.…”
Section: Ambivalent Sexism and Affirmative Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the main literature on citizen support for gender quotas, and more broadly women in politics, do not explore whether citizens might support gender quotas for patronizing, or potentially sexist, reasons (but see Pereira & Porto, 2020). Previous investigations emphasize attitudes toward gender equality (Beauregard, 2018; Gidengil, 1996; Keenan & McElroy, 2017), support for government involvement (Barnes & Córdova, 2016), partisanship and ideology (Dubrow, 2011), elite cues (Morgan & Buice, 2013), or a desire for descriptive and substantive representation (Allen & Cutts, 2016; Bolzendahl & Coffé, 2020) as explanations for quota support. We further explore a crucial set of explanations for understanding gender‐quotas support that nuances the previous understanding that greater commitment toward gender equality should be linked with greater support.…”
Section: Ambivalent Sexism and Affirmative Actionmentioning
confidence: 99%
“…Research has mostly focused on explaining support for legislative quotas (Barnes & Córdova, 2016; Beauregard, 2018; Dubrow, 2011; Gidengil, 1996; Keenan & McElroy, 2017; Pereira & Porto, 2020)—that is, policies promoting constitutional or legislative change to mandate and require political parties to designate a certain percentage of women candidates for election (Krook et al, 2009). Respondents appear more likely to support these policies if they themselves are a potential beneficiary (Bolzendahl & Coffé, 2020), if they have a preexisting commitment to equality (Gidengil, 1996), if they believe that government should be involved to decrease inequalities (Barnes & Córdova, 2016), if they agree that the presence of women provide symbolic benefits (Bolzendahl & Coffé, 2020), or if they want women to have greater substantive representation (Allen & Cutts, 2016). Haley and Sidanius (2006) argue that individuals' response to affirmative action is conditioned both by “prepackaged” conceptualizations of the issue and their existing predilections.…”
Section: Ambivalent Sexism and Affirmative Actionmentioning
confidence: 99%
“…The empirical literature on support for AAP has consistently confirmed this group interest-based explanation (e.g., Harrison et al 2006;Möhring, Teney, and Buss 2019). Furthermore, recent empirical studies have pointed to the fact that members of an underrepresented group are more likely to support AAP targeted at other underrepresented groups than members of the majority group (i.e., white men) (e.g., Bolzendahl and Coffé 2020;Kane and Whipkey 2009;Scarborough, Lambouths, and Holbrook 2019). Therefore, as women belong to an underrepresented group, they might be more likely than men to identify and feel solidarity with other underrepresented groups, such as immigrants 1 : members of an underrepresented group might not only identify with their own group but also perceive communalities with members of other underrepresented groups.…”
Section: Identity Criterion Of Deservingnessmentioning
confidence: 89%
“…Research on citizens’ support in a variety of contexts, however, shows relatively low levels of support (e.g. Barnes and Córdova, 2016; Beauregard, 2018; Bolzendahl and Coffé, 2020; Pereira and Porto, 2020).…”
Section: Theorymentioning
confidence: 99%
“…Mirroring this diffusion of quotas in many democracies, research increasingly focuses on analyzing and explaining support for gender quotas. The available public opinion literature has shown that support for gender quotas is quite mixed across nations, but tends to be relatively low (Barnes and Córdova, 2016; Beauregard, 2018; Bolzendahl and Coffé, 2020; Keenan and McElroy, 2017). Although quotas have been introduced in many countries, they are often considered as controversial (Bacchi, 2006; Teigen and Karlsen, 2020).…”
Section: Introductionmentioning
confidence: 99%